Methods for quantitative evaluation of force and technique in competitive sport climbing - Pandurevic, D.; Sutor, A.; Hochradel, K. (Journal of Physics: Conference Series, 2019)
Increasing media attention of and progress in competitive climbing demand for novel solution in sport analysis to accompany and contribute to the evolution of climbing. We present a holistic approach to acquire movements in sport climbing. Knowledge on force and corresponding body motion helps to understand technique, performance and might even lead to injury prevention during training. Our system allows detection of peaks in force on each climbing hand and foot hold while recording the associated body position and motion. To achieve this, we equipped each hold with a three-axis force sensor and combined this with a three-dimensional markerless motion capture system based on a depth camera. Existing methods to determine finger strength and other parameters such as temperature are employed to ensure comparableand repeatable results. In addition, pre-assesement of athletes will be used to evaluate inter- and intra-individual variability among athletes